Automated preparation of the book of abstracts for scientific conferences using R and LaTeX - Lusa, Lara (Informatica Medica Slovenica, 2009)
The organization of a scientific conference can be a very demanding and timeconsuming duty. Two challenging tasks are the preparation of the detailed program and of the book of abstracts. To make these tasks easier to handle, wedeveloped the generbook package, which includes some functions written in R language and a LaTeX template for the book of abstracts. This paper describes the package and how to use it; it also shows how it was used for the organization of an international statistical conference.
Keywords: Abstracting And Indexing; Abstrahiranje in indeksiranje; Automatic Data Processing; Avtomatska obdelava podatkov; Congresses; International Cooperation; Kongresi; Mednarodno sodelovanje; Raziskava; Research